Serological and immunological study to the prevalence of Toxoplasmosis among sewage workers, soil workers and sellers of fruits and vegetables in the province of Thi-Qar-Iraq - Hammed , Nawader (University of Thi-Qar Journal of Science, 2015)
The current study was performed for the first time in Iraq and in the Thi-Qar province, to estimate the prevalenceof toxoplasmosis among sewage workers, workers in the soil and fruits and vegetables vendor. 300 blood samples were collected from the previous categories which aged between the (10 - >40) years during the period from October 2014 to February 2015 and also 100 blood samples were collected from non-categories previously mentioned (employees) for the purpose of comparison with the current study, by using Enzyme Linked Immunosorbent Assay (ELISA) test to assess the presence of antibodies to the parasite IgM type and IgG and estimate the level of interferon-gamma and Interleukin 27 in the people infect with toxoplasmosis and compared with the control group. Current study show 90 (30%) samples of three categories had seropositive compared with 20 (20%) samples of employers. The current study showed 5 (1.7%) positive cases of IgM's antibody and 76 (25.3%) IgG antibody positive case, while for both IgM + IgG together 9 (3%) positive cases were recorded, also the results found a statistically significant difference between the types of antibodies. The highest percentage of infection found in fruits and vegetables vendor with 32.38%, while lowest percentage of infection found in soil workers with 25.77%. The present study recorded a high concentration of both interferon gamma (IFN-ɤ) rate and interleukin-27(IL-27) in the blood of people infected with toxoplasmosis, compared with the control group.